we know taht
the explicit formula for an arithmetic sequence is equal to
![a_n=a_1+d(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/z9jyjzs3gtye2ac99tljhz0dstsxu67bsc.png)
In this problem we have that
![a_n=-7+6n](https://img.qammunity.org/2023/formulas/mathematics/college/8uqn325iqaxkn2a52kh4lqahdk6fsr8nkz.png)
we know that
the distance betwee consecutive numbers is 6
that means
the common difference is d=6
substitute the value of d in the first equation
![\begin{gathered} a_n=a_1+6(n-1) \\ a_n=a_1+6n-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/42pmb926ii1m8fipa112zgiijes5wpxlvr.png)
Equete both equations